Aging, society, and the life course - Morgan, Leslie A. (Springer Pub., 2011)
This is a comprehensive textbook for both undergraduate and graduate level courses, detailing the impact of societal forces on the aging process. The book focuses on the diversity of the older population, examining it from micro/macro perspectives in order to understand aging and the life course as social phenomena. This latest edition examines significant changes in the field of social gerontology, such as the paradigms of aging and the life course, the baby boomer cohorts as they approach retirement and later life, the growing interest in global aging, and civic engagement. This text encourages students to examine aging from personal, familial, community, societal and global perspectives, including both the positive and negative realities of aging.